Prevalence of nonmedical methamphetamine use in the United States - Barchha Nina; Crits-Christoph Paul; Kroutil Larry A; Durell Todd M; Van Brunt David L (BMC, 2008)
Abstract Background Illicit methamphetamine use continues to be a public health concern in the United States. The goal of the current study was to use a relatively inexpensive methodology to examine the prevalence and demographic correlates of nonmedical methamphetamine use in the United States. Methods The sample was obtained through an internet survey of noninstitutionalized adults (n = 4,297) aged 18 to 49 in the United States in 2005. Propensity weighting methods using information from the U.S. Census and the 2003 National Survey on Drug Use and Health (NSDUH) were used to estimate national-level prevalence rates. Results The overall prevalence of current nonmedical methamphetamine use was estimated to be 0.27%. Lifetime use was estimated to be 8.6%. Current use rates for men (0.32%) and women (0.23%) did not differ, although men had a higher 3-year prevalence rate (3.1%) than women (1.1%). Within the age subgroup with the highest overall methamphetamine use (18 to 25 year olds), non-students had substantially higher methamphetamine use (0.85% current; 2.4% past year) than students (0.23% current; 0.79% past year). Methamphetamine use was not constrained to those with publicly funded health care insurance. Conclusion Through the use of an internet panel weighted to reflect U.S. population norms, the estimated lifetime prevalence of methamphetamine use among 18 to 49 year olds was 8.6%. These findings give rates of use comparable to those reported in the 2005 NSDUH. Internet surveys are a relatively inexpensive way to provide complimentary data to telephone or in-person interviews.